RESEARCH TRENDS ON PARENTAL READINESS IN RAISING CHILDREN WITH DOWN SYNDROME: A BIBLIOMETRIC ANALYSIS - Nurul Sallyna Rostam; SYAR MEZEE Mohd Rashid (LPPM IAD Probolinggo, 2025)
This study examines the intellectual structure and research trends of social science publications on Down syndrome parents. Scopus data on English-language sociology journal articles was used for a bibliometric analysis. Descriptive indicators and visualization were used to identify publication trends, prolific authors, leading countries, influential journals, and dominant research themes. Research output on Down syndrome parental issues has gradually increased, indicating academic interest. Developing nations contributed little to most publications. Keyword analysis revealed parental support, family adaptation, caregiving challenges, and social inclusion as research themes. The findings show gaps in cultural context and parental readiness research in non-Western societies, despite growing literature. This comprehensive review of existing research provides valuable insights for future Down syndrome family studies and policy development.